The Influent of Leadership, Motivation, and Physical Work Environment on Employee Performance - Nur Choliqfatus Azizah; Nur Hidayati; Supriyanto Supriyanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The study aims to analyze the influence of leadership, motivation and physical work environment on employee performance at the Tax Office (KPP) Pratama East Denpasar. The population in this study were all employees of the Pratama Tax Office (KPP) of East Denpasar, namely 96 people, not including the leadership of 1 person. The number of respondents in this study was determined by the census method in which all employees were used as respondents. Data collected through questionnaire method. Furthermore, the data were analyzed using the method of multiple linear regression data analysis techniques. The results of this study are Leadership, Motivation and Physical Work Environment have a significant effect on Employee Performance at East Denpasar KPP, Leadership has a significant positive effect on Employee Performance at East Denpasar KPP, Motivation has a significant positive effect on Employee Performance at East Denpasar KPP. Physical Work Environment has a significant positive effect on Employee Performance at East Denpasar KPP.